Sakralitas Séré Pénang: Simfonik Budaya dan Hukum Islam sebagai Simbol Ketahanan Keluarga di Pamekasan - Alfan Nasrullah, Achmad Muzammil; Elman, Moh.; Busahwi; Mahrus (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2024)
This research aims to capture the efforts of the Madurese people in maintaining family resilience through a cultural approach, as well as to examine the harmony and alignment between the values of the séré pénang tradition as part of the cultural approach and the principles of Islamic law. The research employs a literature review approach, utilizing scholarly sources related to the overarching themes of tradition and Islamic law. The data analysis follows an interactive analysis model. The findings indicate that Madurese people, rich in cultural, traditional, and heritage values, have adopted a cultural approach as part of their efforts to strengthen family resilience. A concrete effort in this regard is the implementation of the séré pénang Tradition, regarded as a symbol of family commitment. This tradition has positive implications for enhancing the resilience of family components to both internal and external pressures. The evaluation of the séré pénang Tradition demonstrates its alignment with the principles of Islamic law, both directly and indirectly, without conflicting with the concepts and principles of Islamic law.